Policy Analysis of the Return of the United States to the Paris Agreement in the Joe Biden Era - Khoirunnisa; Nilam, Nilam Sari (Indonesian Scientific Publication, 2024)
In 2017, under the leadership of Donald Trump, the United States left the Paris Agreement. Substantially, the United States has played a role in reducing global emissions by 21 percent. At the beginning of his tenure, Joe Biden promoted several policies, one of which was the return of the United States to the Paris Agreement. This study is a qualitative research that relies on literature study as its data collection method. Data collection is carried out by searching and compiling information from various sources, such as news analysis, concepts from experts contained in books, scientific works, articles, the internet, or journals relevant to the research theme, with the aim of knowing what is behind the United States returning to the Paris agreement under Joe Biden's leadership, before the United States had left the agreement in addressing climate change. The issue of climate change has a high level of significance for all earthlings. Therefore, Joe Biden at the beginning of his tenure as President immediately made the decision to return to the Paris agreement in overcoming this climate change issue. The author uses the theory of decision making to analyze the problems in this journal. With the return of the United States to the Paris Agreement, it provides major changes in the international world by strengthening global cooperation, encouraging the participation of other countries, influencing energy and economic policies, and restoring the image of the United States as a global leader in the issue of climate change.